PEMBERDAYAAN KADER KESEHATAN REMAJA MELALUI PROGRAM SURYA MUDA DI SMP MUHAMMADIYAH 1 MINGGIR - Zubaida Rohmawati; Siti Khotimah; Zakey Annajhi; Muhammad Radit; Muclas Hendri; Muhammad Zamil Abiyyu; Syifa Aulia Putri (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Adolescents are a strategic group for health promotion because habits formed during this stage often persist into adulthood. However, many adolescents remain insufficiently active, spend long hours on screens, sleep too little, and have limited awareness of posture and simple health monitoring. This community service activity aimed to strengthen adolescent health cadres through the SURYA MUDA program at SMP Muhammadiyah 1 Minggir. The activity involved 10 student cadres and 2 accompanying teachers and was delivered through short lectures, interactive discussion, practical demonstrations, group simulations, and simple health screening. The educational content covered physical activity literacy, posture and ergonomics, sleep hygiene and screen-time management, safe bodyweight exercise, and basic anthropometric and blood pressure checks. Pretest and posttest evaluation showed an increase in the mean score from 85.0 to 87.0. Participants also produced a cadre action plan and demonstrated improved readiness to disseminate healthy behaviour messages in the school environment. The program indicates that a school-based, peer-led, and low-cost approach can strengthen adolescent health promotion while supporting physical and mental well-being.